Diuretic Therapy: Mechanisms, Clinical Applications, and Management - Nicoleta-Mirela Blebea; Ciprian Pușcașu; Emil Ștefănescu; Alina Mihaela Stăniguț (Journal of Mind and Medical Sciences)
Diuretics are a class of pharmacological agents that promote the renal excretion of water and electrolytes, increasing urine output and reducing fluid retention. They play a critical role in the management of edematous syndromes, irrespective of their etiology (cardiac, renal, or hepatic), as well as in the treatment of hypertension (HTA). The mechanism of action of diuretics can be classified as either renal, as seen with saluretic diuretics that inhibit sodium and water reabsorption at various segments of the nephron, or extrarenal, involving alterations in the glomerular filtration pressure or osmotic mechanisms. Based on their site of action and mechanism, diuretics are categorized into multiple classes, including loop diuretics, thiazide and thiazide-like diuretics, potassium-sparing diuretics, carbonic anhydrase inhibitors, and osmotic diuretics. These agents are frequently used in combination with other antihypertensive or heart failure medications to optimize therapeutic efficacy. By reducing the blood volume and peripheral vascular resistance, diuretics improve cardiac function, lower blood pressure, and enhance exercise tolerance. Additionally, they are employed in managing chronic kidney disease (CKD), electrolyte imbalances, and specific metabolic disorders. Given the potential for adverse effects such as electrolyte disturbances and renal dysfunction, diuretic therapy should be individualized, with the careful monitoring of the dosage, patient response, and comorbid conditions. Patient education on adherence, lifestyle modifications, and the recognition of side effects is essential for optimizing the therapeutic outcomes and minimizing the risks associated with diuretic therapy.